2016
DOI: 10.1111/jcmm.12881
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 and AMP‐activated protein kinase contribute to 17‐DMAG‐dependent protection against heat stroke

Abstract: Heat shock protein 70 (Hsp70) preconditioning induces thermotolerance, and adenosine monophosphate (AMP)‐activated protein kinase (AMPK) plays a role in the process of autophagy. Here, we investigated whether 17‐dimethylaminoethylamino‐17‐demethoxy‐geldanamycin (17‐DMAG) protected against heat stroke (HS) in rats by up‐regulation of Hsp70 and phosphorylated AMPK (pAMPK). To produce HS, male Sprague–Dawley rats were placed in a chamber with an ambient temperature of 42°C. Physiological function (mean arterial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Recently, it has been shown in mice that HO‐1‐mediated autophagy protects against hepatocyte cell death and hepatic injury from infection/sepsis . Furthermore, HSP70 has been suggested to activate the autophagic process to protect against heat‐shock stress . In this study, we demonstrated that oestrogen can preserve the capacity of cellular HO‐1 and HSP70 production during endotoxaemia (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Recently, it has been shown in mice that HO‐1‐mediated autophagy protects against hepatocyte cell death and hepatic injury from infection/sepsis . Furthermore, HSP70 has been suggested to activate the autophagic process to protect against heat‐shock stress . In this study, we demonstrated that oestrogen can preserve the capacity of cellular HO‐1 and HSP70 production during endotoxaemia (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…It is worth noting that in mice, the antioxidant enzyme HO‐1‐mediated autophagy protects against hepatocyte cell death and hepatic injury from infection/sepsis . Our previous report revealed that up‐regulation of HSP 70 is associated with activation of autophagy, leading to protection against heat stress . Therefore, in this study, we evaluated the preventive effect of long‐term E 2 replacement on endotoxaemia‐induced septic shock and MODS, such as hepatic and renal dysfunction, rhabdomyolysis and coagulopathy in anaesthetized Ovx rats and further investigated whether activation of autophagy, as well as induction of HO‐1 and HSP70 contribute to the beneficial effects of oestrogen.…”
Section: Introductionmentioning
confidence: 95%
“…After anesthesia (urethane 1.2 g/kg, i.p.) and left femoral arterial and venous cannulation, the rats were randomized into four groups as indicated in Figure 1: (I) normothermal control group (Con): rats were arranged in a heating chamber at room temperature (24°C) for 1 h and maintained throughout the entire experiment ( N = 5); (II) HS group: rats were placed in a heating chamber (42°C) for 40 min until the rectal core temperature (Tco) elevated to 42°C to induce HS, as previously described [21] ( N = 19); (III) ALA40+HS group: HS rats were pretreated with ALA 40 mg/kg (i.p.) (Sigma-Aldrich, St. Louis, MO, USA) at 1.5 h prior to heat stress ( N = 12); (IV) ALA80+HS group: rats were pretreated with ALA 80 mg/kg (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Heat shock proteins (HSP) are a family of proteins produced by nearly all cells in response to stressful conditions, including heat shock as well as other stresses, such as exposure to cold and ultraviolet light [ 6 , 30 ]. Increased levels of HSPs, such as HSP70, are necessary for acquired heat tolerance.…”
Section: Pathogenesismentioning
confidence: 99%
“…Increased levels of HSPs, such as HSP70, are necessary for acquired heat tolerance. Moreover, the overexpression of HSP70 in response to heat stress can protect against organ dysfunction and reduces mortality in rats [ 30 ].…”
Section: Pathogenesismentioning
confidence: 99%